Treatment of Calcaneal Fracture by Calcaneal Plate - Abed Anwar Abd Elfattah (Al-Azhar University, Faculty of Medicine (Damietta), 2021)
Background: Calcaneal fractures are not uncommon, accounting for 2% and 60.0% of all adult and tarsal fractures, respectively. Its treatment is still controversial.  Aim of the work: To assess results and complications of calcaneal fractures treatment by fixation with calcaneal plate on clinical and radiological basis. Patients and Methods: A convenient sample of 20 patients, with calcaneal fractures and treated by calcaneal plate fixation were included. They were assessed in preoperative period in a systematic manner. Then, treated with a locking plate. Postoperatively, immediate X-rays, examination of the neurovascular status had been done. Anti-edematous, pain therapy, intravenous antibiotics and anticoagulation medication were administered.  All patients had been followed up at 8, 16 weeks after operation and assessed for functional and anatomical state. RESULTS: According to the American Orthopedic Foot Ankle Society [AOFAS] Ankle-Hindfoot Score, the outcome was excellent [30.0%], good [40.0%], fair [20.0%] and poor [10.0%].   At the last follow‑up, Bohler’s angle was restored to normal [20°-40°] in 17 feet [85 %] while 3 feet [15 %] was less than normal. Wound infection was seen in [10%], each of varus heel deformity and flexion deformity of big toe was found in one patient [5.0%] and two case had reflex sympathetic dystrophy.Finally, there was no association between fracture type and subtalar arthritis. However, patients with subtalar arthritis had significantly lower AOFAS score when compared to patients with no subtalar arthritis [76.22±6.24 vs 87.0±6.05 respectively, p < 0.001]. Conclusion: Displaced calcaneal fractures treated surgically are associated with a relatively better functional outcome, provided that, Bohler's angle was restored to its normal or near normal values.